Human Sclera Maintains Common Characteristics with Cartilage throughout Evolution - Seko, Yuko (Public Library of Science, 2008)
BACKGROUND: The sclera maintains and protects the eye ball, which receives visual inputs. Although the sclera does not contribute significantly to visual perception, scleral diseases such as refractory scleritis, scleral perforation and pathological myopia are considered incurable or difficult to cure. The aim of this study is to identify characteristics of the human sclera as one of the connective tissues derived from the neural crest and mesoderm. METHODOLOGY/PRINCIPAL FINDINGS: We have demonstrated microarray data of cultured human infant scleral cells. Hierarchical clustering was performed to group scleral cells and other mesenchymal cells into subcategories. Hierarchical clustering analysis showed similarity between scleral cells and auricular cartilage-derived cells. Cultured micromasses of scleral cells exposed to TGF-βs and BMP2 produced an abundant matrix. The expression of cartilage-associated genes, such as Indian hedge hog, type X collagen, and MMP13, was up-regulated within 3 weeks in vitro. These results suggest that human ‘sclera’-derived cells can be considered chondrocytes when cultured ex vivo. CONCLUSIONS/SIGNIFICANCE: Our present study shows a chondrogenic potential of human sclera. Interestingly, the sclera of certain vertebrates, such as birds and fish, is composed of hyaline cartilage. Although the human sclera is not a cartilaginous tissue, the human sclera maintains chondrogenic potential throughout evolution. In addition, our findings directly explain an enigma that the sclera and the joint cartilage are common targets of inflammatory cells in rheumatic arthritis. The present global gene expression database will contribute to the clarification of the pathogenesis of developmental diseases such as high myopia.